Wolves choose ambushing locations to counter and capitalize on the sensory abilities of their prey ... - Gable, Thomas; Homkes, Austin; Johnson-Bice, Sean; Windels, Steve; Bump, Joseph (Dryad, 2020)
Wolves (Canis lupus) are primarily cursorial predators, but they use ambush strategies to hunt beavers (Castor canadensis). Terrestrial beaver activity is predictable because beavers use well-defined, conspicuous habitat features repeatedly. Thus, studying where wolves wait-in-ambush for beavers provides a unique opportunity to understand how predators choose ambush locations in relation to prey activity. We searched 11,817 clusters of GPS-locations from wolves in the Greater Voyageurs Ecosystem, Minnesota, USA and documented 748 ambushing sites and 214 instances where wolves killed beavers. Wolves chose ambush locations: 1) with olfactory concealment to avoid detection from the highly-developed olfactory senses of beavers, and 2) close (generally <5 m) to beaver habitat features to take advantage of beavers’ inability to visually detect motionless predators. Our work describes in detail the ambush strategies wolves use to hunt beavers, and continues to overturn the traditional notion that wolves rely ... : We identified ambushing attempts and wolf-killed beavers by following wolves fitted with 20-minute fix interval GPS-collars. Please see the publication for detailed information on our methods. The data presented is the raw data and has not been processed. ...